Does corporate social responsibility promote the financial performance of the telecom industry in Ghana? - David Mensah Awadzie; David Kwashie Garr; Edward Attah-Botchwey; Kofi Koduah Sarpong; Mensah Marfo (Cogent Business & Management, 2023)
The purpose of this study is to determine how corporate social responsibility (CSR) promotes the financial performance of the telecom industry in Ghana. The study developed the role of mediating and moderating variables such as corporate reputation (CR) and customers' purchasing intention (CPI). This study uses cross-sectional data from the telecom industry in Ghana. The structural equation model was employed through Smart PLS to explain the relationships between CSR and the firm's financial performance. The findings indicate a positive and significant impact of CSR on firms' financial performance. This implies that CSR has a direct relationship with a firm's performance. The study has also revealed that CSR has a positive and significant effect on a firm's performance through the mediating role of CPI. The finding again indicates that CR does not mediate the relationship between CSR and FP. The finding further shows that CPI does not play any moderating role between CSR and a firm's financial performance. This study has added to empirical research to the body of knowledge on CSR and firms' performance in the telecom industry. Entrepreneurs and senior management might use the study's findings to improve a company's success. A valuable contribution to this study is the mediating and moderating impact of CR and CPI, which can be reinforced further in future studies.
Keywords: 650; corporate social responsibility; purchasing intention; Corporate reputation; firms' financial performance; smart PLS